An integrative model of internationalization strategies: The corporate entrepreneurship – institutional environment – regulatory focus (EIR) framework. Issue 3 (1st July 2014) - Li, Xin; Gammelgaard, Jens
Abstract : Purpose: – This paper aims to critically review the ownership, location and internalization (OLI) model and the Uppsala internationalization process (UIP) framework. We suggest that the inclusion of concepts such as corporate entrepreneurship, host country institutions and regulatory focus in an integrated framework helps to explain firm internationalization. Design/methodology/approach: – This paper is based on a review of the literature on the OLI and UIP models. In addition, it presents a conceptual model that encompasses corporate entrepreneurship, regulatory focus and institutions. Findings: – The OLI and the UIP models fail to include corporate entrepreneurship and managerial psychology in their analyses. We suggest that regulatory focus theory unifies the managerial strategic choice between position logic and opportunity logic. In addition, host country institutions affect this managerial choice with regard to internationalization. Practical implications: – Regulatory focus theory originates from managerial psychology. The model is, therefore, relevant for managers, and it shows how the outcomes and processes of corporate entrepreneurial activity should manifest themselves in managerial decision-making related to further internationalization. The strength of host country institutions also affects such decision-making. Originality/value: – This paper is the first to present the concept of regulatory focus in relation to firm internationalization. In addition, it shows that most entrepreneurship-related models of internationalization focus on international entrepreneurship and start-up firms. In contrast, this paper focuses on corporate entrepreneurship and the internationalization of established firms.